Chemico-genetic discovery of astrocytic control of inhibition in vivo - Takano, Tetsuya (Nature, 2020)
Perisynaptic astrocyte processes are an integral part of central nervous system synapses(1,2); however, the molecular mechanisms governing astrocyte-synapse adhesions and how astrocyte contacts control synapse formation and function are largely unknown. Here we develop an in vivo chemico-genetic approach, Split-TurboID, that uses a cell surface fragment complementation strategy. We thus identify a proteome enriched at astrocyte-neuron junctions in vivo, including Neuronal Cell Adhesion Molecule (NrCAM). We find that NrCAM is expressed in cortical astrocytes, localized to perisynaptic contacts and is required to restrict neuropil infiltration by astrocytic processes. Furthermore, we show that astrocytic NrCAM transcellularly interacts with neuronal NrCAM that is coupled to gephyrin at inhibitory postsynapses. Depletion of astrocytic NrCAM significantly reduces inhibitory synapse numbers without altering glutamatergic synaptic density. Moreover, loss of astrocytic NrCAM dramatically reduces inhibitory synaptic function with minor effects on excitation. Thus, our results present a proteomic framework for how astrocytes interface with neurons, and reveal how astrocytes control GABAergic synapse formation and function.